Case Report: Bilateral adrenal hemorrhage and hemophagocytosis in the reticuloendothelial system caused by Escherichia coli in a young woman: an autopsy case - Tanaka, Yudai; Hayashi, Koji; Kawahara, Ei; Azuma, Shin-Ichiro; Hayashi, Maho; Nakaya, Yuka; Suzuki, Asuka; Ueda, Midori; Asano, Rei; Hayashi, Hiromi; Miura, Toyoaki; Hayashi, Kouji; et al. (Frontiers in Medicine, 2025)
BackgroundSepsis can lead to life-threatening complications such as hemophagocytic lymphohistiocytosis (HLH) and bilateral adrenal hemorrhage (BAH), commonly known as Waterhouse-Friderichsen syndrome. HLH involves severe inflammation and organ damage, often linked with infections and autoimmune diseases, while BAH leads to adrenal insufficiency, typically caused by Neisseria meningitidis, though Escherichia coli (E. coli) is a rare cause.Case presentationA 27-year-old Japanese woman, with a history of diabetes mellitus and obesity, presented with a complicated urinary tract infection. She commenced oral levofloxacin treatment five days before hospital admission. Her medications included prednisolone 5 mg/day, trimethoprim-sulfamethoxazole for pyoderma gangrenosum, and oral hypoglycemic agents. Upon admission, her vital signs, including body temperature and blood pressure, were stable, and her body mass index was recorded at 49.8. Laboratory tests indicated elevated white blood cell count and C-reactive protein. She was diagnosed with a urinary tract infection and was treated with levofloxacin and trimethoprim-sulfamethoxazole. On day 16 of hospitalization, her general condition rapidly worsened, leading to her sudden death on day 18. Premortem blood tests showed cytopenia, and blood cultures tested positive for E. coli. Autopsy imaging using computed tomography revealed enlargement and high density of the left adrenal gland. Postmortem pathology identified bilateral adrenal hemorrhages with focal necrosis. Extensive erythrophagocytic macrophages were observed in the bone marrow, spleen, and liver. Disseminated intravascular coagulopathy was confirmed through the detection of a renal glomerular fibrin thrombus.ConclusionWe concluded that E. coli infection had caused multiple fatal conditions, such as disseminated intravascular coagulopathy, bilateral adrenal hemorrhage, and suspected hemophagocytic lymphohistiocytosis leading to the death of the young woman.